2022
DOI: 10.1097/mol.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein (a) in familial hypercholesterolaemia

Abstract: Purpose of reviewThe role of lipoprotein (a) in atherogenesis has been the subject of argument for many years. Evidence that it is raised in familial hypercholesterolaemia has been disputed not least because a mechanism related to low density lipoprotein (LDL) receptor mediated catabolism has been lacking. Whether lipoprotein (a) increases the already raised atherosclerotic cardiovascular disease (ASCVD) risk in familial hypercholesterolaemia is also more dubious than is often stated. We review the evidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A genome-wide association study (GWAS) identified an intronic variant in LPA locus (rs10455872) associated with cardiovascular risk in patients taking statins [33]. Heterozygous FH patients had higher Lp(a) levels than the general population, which contributes to increased risk of cardiovascular events [34,35].…”
Section: Association Of Deleterious Variants With Ldlc Response To St...mentioning
confidence: 99%
“…A genome-wide association study (GWAS) identified an intronic variant in LPA locus (rs10455872) associated with cardiovascular risk in patients taking statins [33]. Heterozygous FH patients had higher Lp(a) levels than the general population, which contributes to increased risk of cardiovascular events [34,35].…”
Section: Association Of Deleterious Variants With Ldlc Response To St...mentioning
confidence: 99%